2005
DOI: 10.1128/iai.73.7.4081-4087.2005
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Insertional Events, Restricted by the Genetic Background, Have Led to Acquisition of Pathogenicity Island II J96 -Like Domains among Escherichia coli Strains of Different Clinical Origins

Abstract: We investigated the dissemination of pathogenicity island (PAI) II J96 -like elements (hra, hly, cnf1, and pap) among 455 Escherichia coli isolates from children and adults with urinary tract infection (UTI), neonates with meningitis or colonized healthy neonates, and 74 reference strains by means of PCR phylogenetic grouping, ribotyping, and PCR analysis of virulence genes. Colocalization of these genes was documented by pulsed-field gel electrophoresis followed by Southern hybridization and long-range PCR (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…We also confirmed previous knowledge about the genes mostly present in all isolates (fimA), those nearly absent both in non-B2 isolates and in resistant isolates (hlyA and cnf1, which show a physical linkage in PAI II J96 ) (4,38,41), and the intermediate percentages of papC presence (8,16,22,23,33,44).…”
Section: Discussionsupporting
confidence: 76%
“…We also confirmed previous knowledge about the genes mostly present in all isolates (fimA), those nearly absent both in non-B2 isolates and in resistant isolates (hlyA and cnf1, which show a physical linkage in PAI II J96 ) (4,38,41), and the intermediate percentages of papC presence (8,16,22,23,33,44).…”
Section: Discussionsupporting
confidence: 76%
“…Because of the general genetic content of prf fimbrial and hlyCABD virulence genes, this island has also been identified as PAI I C5 and PAI II J96 (5,8,22). The prf fimbria-and hlyCABD-containing island does vary in significant ways because the dsdCXA, hra, and cnf-1 loci are not consistently present.…”
Section: Discussionmentioning
confidence: 99%
“…Bidet et al (6) categorized their STEC isolates, like O157:H7, into group D and showed that cattle are the main reservoir. There are few studies about the phylogenetic affiliation of STEC and EPEC strains isolated from goats.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis have indicated that E. coli can be categorized into four major phylogenetic groups (A, B1, B2, and D) which can be divided into seven subgroups A 0 , A 1 , B1, B2 2 , B2 3 , D 1 and, D 2 using a rapid polymerase chain reaction (PCR)-based method for the detection of chuA (the outer-membrane hemin receptor gene), yjaA (the gene encodes an uncharacterized protein) and TSPE4.C2 (an anonymous DNA fragment) (2)(3)(4)(5). Recently, relationships have been demonstrated between E. coli phylogenetic characteristics and obtaining virulence genes (6,7). Virulence factors may be found more commonly in strains of groups B2 and D, whereas majority of A and B1 strains are nonpathogenic and isolated from nondiarrheic fecal samples (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%